The relationship between cognitive flexibility, depression, and work performance: Employee assessments using cognitive flexibility tests - Toshiki Fukuzaki; Shinya Takeda (Journal of Affective Disorders Reports, 2022)
Background: Cognitive flexibility is a frontal lobe function, and some scholars have indicated that it is linked to depression. The Cognitive Flexibility Test (CFT) is a neuropsychological test that can easily and promptly measure cognitive flexibility within a short amount of time. This study focuses on healthy younger workers to determine the associations between their cognitive flexibility, depression, and performance at work. Methods: The absolute absenteeism and the absolute presenteeism of a group of 80 regular employees were measured, and the employees were administered the Verbal Fluency Test (VTF), the CFT-A and CFT-B, the Beck Depression Inventory-II (BDI-2), and the World Health Organization Health and Work Performance Questionnaire (WHO-HPQ). Google Forms were used to measure the BDI-2, absolute absenteeism, and absolute presenteeism, and online interviews were conducted on Zoom to collect answers to the CFT and the Verbal Fluency Test (VFT). Results: No significant age-related differences appeared in the number of responses obtained for the CFT-A and CFT-B from subjects grouped according to the decades they represented, ranging from the 20s to the 50s. In addition, the CFT-A and CFT-B did not indicate significant correlations between the BDI-2 and absenteeism and presenteeism. Limitations: Small sample, online vs. in person assessments due to COVID-19. Conclusion: The results suggest that the function of cognitive flexibility is relatively stable and is unaffected by age brackets. The study also found no links between the cognitive flexibility of healthy young workers, the state of depression, or their work performance.